Crafted ambiguity in the Wisdom of Solomon - Zurawski, Jason (Journal for the study of the pseudepigrapha, 2021)
The Wisdom of Solomon is a text intensely concerned with epistemological questions. What is true knowledge? Where does it come from? What’s its purpose? How does one attain it? In each of its parts, Wisdom can be seen directly and clearly tackling these types of problems. The Wisdom of Solomon is also a text deeply and frustratingly ambiguous. Is this some kind of embarrassing irony, a text so intent on delving into the nature and purpose of understanding ultimately unable to be understood? This study looks at how the ambiguity, surely present at several places throughout the book, is, in fact, rhetorically crafted and designed to guide to the reader to greater clarity and understanding. There is, then, no conflict between the stated purpose of the text, to lead the reader to wisdom and knowledge, and the means by which the author does so. The ambiguity and the epistemology of the Wisdom of Solomon are, in the end, inseparable.